A CAD system for heterogeneous solid modelling. (28th November 2005) - Tandon, Puneet; Kant, Anuj
Objects that are made up of multiple materials and known as heterogeneous objects are now increasingly being used in engineering applications. The development of new fabrication methods like rapid prototyping (RP), calls for new techniques to manufacture these objects. To manufacture heterogeneous objects by RP, a CAD model is required that contains both geometric information as well as material information. However, current solid modelling techniques focus mainly on capturing the geometric information only. This work presents an approach to model and represent heterogeneous objects by integrating the material information along with the geometry/topology in the solid model. New modelling operations are defined for creating and manipulating heterogeneous models. The approach will be helpful in developing the manufacturing strategy using advanced technological tools.